Fruit Quality of Guava (Psidium guajava ‘Kristal’) under Different Fruit Bagging Treatments and Altitudes of Growing Location - Widyastuti, R.A.D.; Budiarto, Rahmat; Hendarto, Kus; Warganegara, Hayane Adeline; Listiana, Indah; Haryanto, Yoyon; Yanfika, Helvi (Journal of Tropical Crop Science, 2022)
Fruit quality is an important aspect that requires attention and more study when it comes to commercializing tropical fruits, including guava ‘Kristal’. This study aimed to evaluate the effect of bagging treatment and altitude of growing orchard on fruit quality of guava (Psidium guajava var. ‘Kristal’). This study was conducted at two local orchards managed by small-scale farmers, at Gunung Batu (1000 meters above sea level, m asl) and Brajaselebah (25 m asl), Lampung Province, Indonesia. A nested design was applied to test 5 types of bagging treatments and 2 levels of land altitude. Fruit quality was assessed by measuring both physical and chemical characteristics. Fruit size indicated by fruit weight and diameter was significantly larger in lowland compared to highland. The total soluble solids (TSS) were significantly higher in the lowland compared to the highland, while titratable acid (TA) showed an opposite result. Vitamin C of the fruits varied from140 to 146 mg per 100 g. Different types of fruit bagging and land altitudes did not affect the physical and chemical characteristics of “Kristal” guava fruits. Fruit scar intensity was higher in lowland, especially in fruit without bagging. Fruit bagging is highly recommended for farmers due to the success of this treatment to reduce fruit scar intensity, thus resulting in good fruit quality, irrespective of the growing locations.